Cultural Globalization and Sustainable Peace - Ghezelsofla, Mohammad-Taghi; Sayady, Hasty (Technium Social Sciences Journal, 2020)
Preventing war and expanding international peace has always been one of the major concerns of the scientific and academic circles of international relations and therefore the recognition of nature and discourse governing international relations is of particular importance. On the other hand, the new phenomenon of globalization is a very influential element in the relations between the state and social forces which has particularly affected the human political social and cultural arenas in the past two decades. And in the meantime international peace can spread as much as possible through the expansion of cultural ties. Therefore the present paper seeks to explore the role of globalization of political culture in global peace expansion as one of the new areas in studies related to globalization. Obviously the present paper seeks to answer the question of how the globalization of political culture has had an impact on international peace. In general, the main reasoning behind the present study is to look at the phenomenon of globalization from the point of view of contemporary modernity that the globalization of political culture by creating a series of common values ??and norms have reduced the ideological contradictions that were the root of most of the warfare of human history and as a result has strengthened international peace.